The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5604/01.3001.0010.2713
|View full text |Cite
|
Sign up to set email alerts
|

Models of non-Alcoholic Fatty Liver Disease and Potential Translational Value: the Effects of 3,5-L-diiodothyronine

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common liver disorder in industrialized countries and is associated with increased risk of cardiovascular, hepatic and metabolic diseases. Molecular mechanisms on the root of the disrupted lipid homeostasis in NAFLD and potential therapeutic strategies can benefit of in vivo and in vitro experimental models of fatty liver. Here, we describe the high fat diet (HFD)-fed rat in vivo model, and two in vitro models, the primary cultured rat fatty hepatocytes or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 79 publications
2
40
0
Order By: Relevance
“…Several rodent models for NAFLD have been developed [113][114][115], including high-fat cholesterol (HFC) and methionine-and choline-deficient (MCD) diet-induced or genetic deficient models, including leptin-deficient ob/ob, leptin receptor-deficient db/db mice, and fa/fa rats. Several preclinical studies were conducted to investigate the effects of NAFLD on bile acid homeostasis using NAFLD mouse or rat models.…”
Section: Altered Bile Acid Profiles In Nafld Animal Modelsmentioning
confidence: 99%
“…Several rodent models for NAFLD have been developed [113][114][115], including high-fat cholesterol (HFC) and methionine-and choline-deficient (MCD) diet-induced or genetic deficient models, including leptin-deficient ob/ob, leptin receptor-deficient db/db mice, and fa/fa rats. Several preclinical studies were conducted to investigate the effects of NAFLD on bile acid homeostasis using NAFLD mouse or rat models.…”
Section: Altered Bile Acid Profiles In Nafld Animal Modelsmentioning
confidence: 99%
“…It was widely used in experimental animals to model human NAFLD. 20 As previously described, [21][22][23] in the model of NAFLD high-fat diet feeding induced body weight and liver weight, increased epididymal and perirenal fat accumulation (Table 4). Moreover, mice fed with high-fat diet showed signicantly higher plasma total cholesterol and AST, ALT levels in comparison with control mice (+58%, +465%, +83%, respectively, vs. control) ( Table 4).…”
Section: Applicationmentioning
confidence: 71%
“…Notably, treatment of steatotic FaO cells with 3,5-T2 or T3 for 24 h reduced TAG content as well as the number and size of LDs. The effects of 3,5-T2 were also accompanied by a reduction of PPARγ [282,283]. These findings demonstrated that the direct hypolipidizing effect exerted both by 3,5-T2 and T3 on the hepatic cells can occur even in the absence of TRs [264,265,282] and are based on the ability to activate pathways affecting TAG deposits within LDs and to promote mitochondrial oxidation and/or exocytosis of the very low density lipoproteins (VLDL) [284].…”
Section: The 35-t2 and Lipid Metabolismmentioning
confidence: 78%
“…The effects of 3,5-T2 were also accompanied by a reduction of PPARγ [282,283]. These findings demonstrated that the direct hypolipidizing effect exerted both by 3,5-T2 and T3 on the hepatic cells can occur even in the absence of TRs [264,265,282] and are based on the ability to activate pathways affecting TAG deposits within LDs and to promote mitochondrial oxidation and/or exocytosis of the very low density lipoproteins (VLDL) [284]. The 3,5-T2-mediated effects in steatotic hepatocytes in culture also include the recruitment to LDs of the adipose triglyceride lipase (ATGL), which might be an early mediator of iodothyronine action [282,285].…”
Section: The 35-t2 and Lipid Metabolismmentioning
confidence: 89%
See 1 more Smart Citation